Implementasi Kebijakan SPP-IRT oleh Dinas Kesehatan Kabupaten/Kota di Provinsi Jawa Barat - Dewi, Retno Anggrina Khalistha; Tio, Yohana Tania; Nuraida, Lilis; Rahayu, Winiati P. (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2025)
The Certificate of Fulfillment of Home Industry Processed Food Production Commitments (SPP-IRT) is a legal authorization granted to home industries (IRTP) to produce and distribute processed food products (P-IRT). This study aimed to evaluate the suitability of SPP-IRT issuance in West Java Province and to identify the obstacles encountered in its implementation across different regions. The research was conducted using survey data from 17 respondents, each representing a District/City Health Office in West Java. The level of implementation was categorized into four groups—appropriate, moderately appropriate, less appropriate, and not appropriate—based on scores for main and additional criteria. The District/City Health Offices in West Java achieved 96.47% compliance with the main monitoring criteria and 94.12% compliance with the additional criteria. Fourteen health offices (82.35%) were categorized as appropriate, while three (17.65%) were categorized as less appropriate. The main obstacles reported by the District/City Health Offices included limited human resources, insufficient time, and inadequate budgets. Suggested solutions included increasing the number of certified food safety instructors and district food inspectors, improving time management and work prioritization, and optimizing budget allocation.